2015
DOI: 10.1638/2015-0128.1
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole Toxicity in Multiple Penguin Species

Abstract: Aspergillosis is a common respiratory fungal disease in penguins managed under human care. Triazole antifungal drugs, including itraconazole, are most commonly used for treatment; however, itraconazole treatment failures from drug resistance are becoming more common, requiring newer treatment options. Voriconazole, a newer triazole, is being used more often. Until recently, no voriconazole pharmacokinetic studies had been performed in penguins, leading to empiric dosing based on other avian studies. This has l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…These differences may result in drug toxicity in individuals due to large differences in achieved voriconazole plasma concentrations. Twenty‐four cases of suspected voriconazole toxicity in six species of penguin have been reported by Hyatt and co‐workers (Hyatt et al., ). Clinical signs of toxicity included anorexia, abnormal behavior (lethargy, changes in mentation, depression, isolating self, staring off into the distance), or neurologic signs (weakness, ataxia, paresis, apparent changes in vision, seizure‐like activity, and seizures) in penguins and elevated liver enzymes and bile acids in other birds (Hyatt et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences may result in drug toxicity in individuals due to large differences in achieved voriconazole plasma concentrations. Twenty‐four cases of suspected voriconazole toxicity in six species of penguin have been reported by Hyatt and co‐workers (Hyatt et al., ). Clinical signs of toxicity included anorexia, abnormal behavior (lethargy, changes in mentation, depression, isolating self, staring off into the distance), or neurologic signs (weakness, ataxia, paresis, apparent changes in vision, seizure‐like activity, and seizures) in penguins and elevated liver enzymes and bile acids in other birds (Hyatt et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Hyatt et al. (), signs of toxicity in penguins occurred within 4 to 99 days of start of treatment in animals dosed at least once daily and after 448 and 511 days of treatment in penguins treated every 72 hr and doses in excess of 5 mg/kg were used in all cases. Plasma voriconazole in the affected penguins ranged from >10 to 64.17 μg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…32 Treatment for aspergillosis with VCZ was associated with neurologic events and death in multiple individuals from six penguin species. 37 The authors observed the following adverse clinical signs in the VCZ treated penguins: anorexia, lethargy, weakness, ataxia, paresis, apparent vision changes, seizure-like activity, and generalized seizures. 37 The penguins' plasma concentration levels ranged from 8 to 64 μg/ml, and the birds that had levels above 30 μg/ml exhibited more severe neurologic events.…”
Section: Birdsmentioning
confidence: 99%
“…The taxonomy of Aspergillus is in flux, and four to eight subgenera, and from 16 to 25 sections, has been proposed by different authors, and more than 350 species. Most species are found in the Azoles such as itraconazole (ITC), voriconazole (VRC), posaconazole (POS) and isavuconazole (ISA) are the drugs of choice for prophylaxis and treatment of aspergillosis both in humans and animals [7][8][9][10][11][12]. Because of the difficulty on designing antifungal drugs that lack side effects in humans, effective therapeutic options to treat mycoses presently are limited [13].…”
Section: Aspergillusmentioning
confidence: 99%